Accessibility Analysis of Cyclone Shelters - A Case Study for Atulia Union, Satkhira, Bangladesh (Journal of the Asiatic Society of Bangladesh, Science, 2020)
Cyclone shelters are considered as a solution to reduce cyclone risk in coastal districts of Bangladesh. The location of a shelter plays a crucial part in a potential user’s decisionmaking process. If the perception is that the shelter is too far away, the user may decide not to use it. On the other hand, it would not be financially feasible to construct shelters near every settlement cluster. Therefore, network analysis using GIS has been applied to reveal the optimal location. Apart from distance, there are some other factors (like space, presence of gender segregated rooms and toilets, ramped access way, availability of drinking water, etc.), which affect a user’s affinity to evacuate to a specific shelter. All the shelters in Atulia Union from Satkhira District of Bangladesh were visited to identify these characteristics. Finally, an index was developed to determine the preference of each shelter to its potential users. It was found that there is inadequate number of shelters in the study area and two new shelter locations were recommended.J. Asiat. Soc. Bangladesh, Sci. 46(2): 163-178, December 2020